Penerapan Pendekatan Konseling Behavioral Sebagai Salah Satu Upaya Mengatasi Kenakalan Remaja - Septiria Fiona Palembangan; Debianto Taruk Tiku; Apriliani Batara; Yulianti Milenia Putri (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research is library research or research using library methods. The technique used to collect data is to use sources originating from books and journals that are related to the behaviorist counseling approach. The type of research used in this study is qualitative research which describes the importance of behavioristic counseling approaches and steps in dealing with juvenile delinquency. This research aims to provide an understanding regarding the behavioristic counseling approach in minimizing juvenile delinquency, especially in Sangalla District.